Kemampuan Membaca Intensif Teks Fiksi Siswa Kelas X MAN 2 Kota Makassar (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This research aims to describe the ability to determine information in intensive reading of fiction texts in Class X MAN 2 Makassar City students; to describe the ability to interpret information in intensive reading of fiction texts in Class X MAN 2 Makassar City students; and to describe the ability to evaluate information in intensive reading of fiction texts in Class X MAN 2 Makassar City students. The variables used are the ability to determine information, interpret information, and the ability to evaluate information of Class X MAN 2 Makassar City students. The population in this study were all 12 Class X MAN 2 Makassar City students, while the sample was 2 classes, namely Class X-7 and Class X-11 with a total of 80 students. The research data was obtained by giving a multiple choice test consisting of 25 questions. The data analysis technique is descriptive statistics. Based on the results of descriptive statistical analysis, it was found that the ability to determine information for Class X MAN 2 Makassar City students was very capable; the information interpretation ability of Class X MAN 2 Makassar City students is very capable; and the information evaluation ability of Class X MAN 2 Makassar City students is very capable.